Biogas Production from Benincasa Hispida Waste - Noor Fiza Asiqin, Mohd Ramlan (2013)
Biogas is the mixture of gaseous that generated from the decomposition of organic matter in the absence of oxygen. It consists of methane, carbon dioxide, hydrogen and traces level of other gases. Agricultural wastes where available abundantly in Malaysia serve as one of the potential carbon sources to be utilize to produce biogas.Various sources of agricultural wastes had been investigated their potential in producing biogas. This work will focus on the utilization of Benincasa hispida or also known as Kundur and its potential to produce biogas with cow dung slurry as inoculum. Characterization of Kundur wastes and cow dung slurry for TS, TVS, initial pH, COD and NH3-N are studied. This work also focused on the determination of optimum composition of Kundur waste for the anaerobic digestion. The study was carry out in 2L digester at mesophilic temperature range with total solid concentration of 10% TS and inital pH of about 7. Percent composition of sample A(100wt % Kundur waste) , B(80 wt % Kundur waste:20 wt % Cow dung) , C(60 wt % Kundur waste:40 wt % Cow dung), D(50 wt % Kundur waste:50 wt % Cow dung) and E(40 wt % Kundur waste:60 wt % Cow dung) were used. Sample D shown the most suitable composition with the highest biogas yield of 2.34ml/gTS followed by sample C of 1.46ml/gTS, sample E of 1.16mg/gTS, sample B of 0.3ml/gTS while sample A shown no production of biogas. The different compositions of Kundur waste and cow dung in anaerobic digestion influenced the total biogas production. This lead to a new degree of information Kundur waste are suitable to be used as substrate for biogas generation with the addition of cow dung as inoculum.